Auditory spatial cueing reduces neglect after right-hemispheric stroke: A proof of concept study. (March 2022) - Kaufmann, B.C.; Cazzoli, D.; Bartolomeo, P.; Frey, J.; Pflugshaupt, T.; Knobel, S.E.J.; Nef, T.; Müri, R.M.; Nyffeler, T.
Abstract: Spatial neglect after right-hemispheric stroke, characterized by the failure to attend or respond to the contralesional space, is a strong negative outcome predictor. Neglect is a supramodal syndrome affecting not only the visual but also the auditory modality. Preliminary studies used this audio-visual cross-modal effect to show short-lasting effects on attention towards the neglected space. The aim of the present study was to introduce a new technique of auditory stimulation combining the unspecific effect of music (i.e., patients choose their preferred music) with the effects of auditory spatial cueing (i.e., the music is presented dynamically as moving from right to left). The effect of this new auditory stimulation technique was investigated in two proof-of-concept experiments using repeated-measures, cross-over designs including 21 patients with visual neglect after a first right-hemispheric stroke. In Experiment I (n = 9), neglect patients showed a significantly larger improvement in Letter Cancellation after listening to preferred music with than without auditory spatial cueing . After granting the feasibility of this new auditory stimulation technique, we investigated the long-term aftereffects in Experiment II (n = 12). Herefore, we used video-oculography during Free Visual Exploration, a sensitive and reliable tool to assess spatial attention over time. Listening to music with auditory spatial cueing – as compared to music without auditory spatial cueing – significantly improved neglect severity in terms of visual exploration behaviour for up to 3h. A voxel-based-lesion-symptom mapping analysis over all patients revealed that the response variability in listening to music with auditory spatial cueing is determined by the integrity of the right inferior parietal lobule, the second branch of the superior longitudinal fascicle, and parieto-parietal callosal fibres. Our study shows that listening to music with auditory spatial cueing significantly reduces neglect severity and has the potential to be used as an add-on in the neurorehabilitation of neglect.